2007
DOI: 10.1128/jvi.02727-06
|View full text |Cite
|
Sign up to set email alerts
|

Vif Counteracts a Cyclophilin A-Imposed Inhibition of Simian Immunodeficiency Viruses in Human Cells

Abstract: Vif is a primate lentiviral accessory protein that is crucial for viral infectivity. Vif counteracts the antiviral activity of host deaminases such as APOBEC3G and APOBEC3F. We now report a novel function of African green monkey simian immunodeficiency virus (SIVagm) Vif that promotes replication of SIVagm in human cells lacking detectable deaminase activity. We found that cyclophilin A (CypA) was excluded from wild-type SIV particles but was efficiently packaged into vif-deficient SIVagm virions. The presence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 59 publications
3
12
0
Order By: Relevance
“…Also, the observation that proteasome inhibitors partially rescue reverse transcription of Vpx-deficient viruses in DCs is consistent with the idea that SIVmac virions may be targeted by a TRIM5α-like restriction, or by another E3 ubiquitin ligase in monocyte-derived cells [8]. Whereas these observations raise the possibility that Vpx could act by counteracting TRIM5α, we note that this is not likely, because TRIM5α is expressed in Jurkat T cells [29], which we found not to restrict Vpx-deficient SIVmac virions.…”
Section: Discussionsupporting
confidence: 88%
“…Also, the observation that proteasome inhibitors partially rescue reverse transcription of Vpx-deficient viruses in DCs is consistent with the idea that SIVmac virions may be targeted by a TRIM5α-like restriction, or by another E3 ubiquitin ligase in monocyte-derived cells [8]. Whereas these observations raise the possibility that Vpx could act by counteracting TRIM5α, we note that this is not likely, because TRIM5α is expressed in Jurkat T cells [29], which we found not to restrict Vpx-deficient SIVmac virions.…”
Section: Discussionsupporting
confidence: 88%
“…Cell lysates were prepared from the target LuSIV cells 24 h post-infection, and luciferase activity was measured to assess the efficiency of SIV infection (Figure 2A). Similar to the results in Jurkat cells [27], CsA treatment of either the producer cells or the target cells resulted in suppression of HIV-1 infection confirming the importance of CypA both in producer and target human cells for efficient HIV-1 replication [16,30]. In contrast, SIVagm infection was not inhibited but rather enhanced by CsA treatment of target cells although it was decreased by CsA treatment of producer cells.…”
Section: Resultssupporting
confidence: 76%
“…A recent study has shown a suppressive effect of CypA on replication of vif -deleted SIV in human Jurkat cells, which was counteracted by SIV Vif inhibiting CypA incorporation during virus assembly [27]. This Vif function can be distinguished from its anti-human APOBEC3G (apolipoprotein B mRNA-editing enzyme-catalytic subunit 3G) function.…”
Section: Introductionmentioning
confidence: 99%
“…For example, similar to our findings with Cpr1p CypA-like proteins and Cyp40 homologs, cyclophilins have been shown to inhibit accumulation of several RNA viruses, including influenza A virus, West Nile virus, alfanodaviruses, and HIV-1 (5,52,69). Interestingly, HIV targets CypA via the retroviral Vif protein, which inhibits the incorporation of CypA into the viral particles (70). Overall, cyclophilins are potent inhibitors of several RNA viruses, and they might be part of the innate response of the host against some viruses.…”
Section: Discussionsupporting
confidence: 72%